Thyrotoxic hypokalemic periodic paralysis with cardiac arrhythmia: case report - de Araujo Falcão Amaral, Anamaria (2022)
Objective: To describe the clinical picture of a 35-year-old patient who presented with hypokalemic periodic paralysis due to thyrotoxicosis, followed by cardiac arrhythmia in anemergency room. The patient had no previous diagnosis of hyperthyroidism. Case report: Male patient, x years, with no previous diagnosis of hyperthyroidism, was admitted to the emergency room with flaccid tetraparesis. Five hours after admission, he developed sudden worsening of symptoms and unstable supraventricular tachycardia due to hypokalemia. The condition was reversed and, one month after the episode, he presented a new condition of paresisin the lower limbs, when he was diagnosed with hypokalemic periodic paralysis due to thyrotoxicosis. Conclusion: The fast identification of thyrotoxic hypokalemic periodic paralysis is of fundamental importance, as the patient may have an unfavorable evolution, with imminent risk of death. Improvement occurs after correction of hypokalemia, which must be promptly identified.